Filsafat Ilmu dan Pengaruhnya Terhadap Pengembangan Kurikulum dalam Pendidikan Islam - Izzah, Ikfina Nurul; Nugraha, Mulyawan Safwandy (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the role of the philosophy of science in developing Islamic education curricula and integrating religious and general sciences. Grounded in revelation, reason, and empirical experience, the philosophy of science provides an epistemological basis for enhancing intellectual intelligence while strengthening learners' moral and spiritual character. Using a qualitative approach and library research methods, the study analyzes key concepts and their application in Islamic education. The findings show that the philosophy of science contributes to building holistic curricula that bridge the gap between religious and general sciences while addressing modernization and globalization challenges. It also fosters an education system rooted in Islamic values, adaptable to contemporary changes. The study concludes that the philosophy of science is crucial not only for addressing current educational challenges but also for preserving Islamic identity in education.